Macro-fungal diversity and nutrient content of some edible mushrooms of Nagaland, India - RAJESH KUMAR; ASHWANI TAPWAL; SHAILESH PANDEY; RAJIB KUMAR BORAH; DEVAPOD BORAH; JAYASREE BORGOHAIN (Nusantara Bioscience, 2013)
Abstract. Kumar R, Tapwal A, Pandey S, Borah RK, Borah DP, Borgohain J. 2013. Macro-fungal diversity and nutrient content of some edible mushrooms of Nagaland, India. Nusantara Bioscience 5: 1-7. The northeast region of India abounds in forest wealth, including variety of flora and fauna. The high humidity during monsoon period provides ideal atmospheric conditions for the growth of diverse group of macrofungal fruit bodies. Nagaland, the northeastern state of India is rich in biodiversity and encompasses large numbers of edible and non-edible mushroom species. Young and matured carpophores of 15 wild edible mushroom species were collected from 12 locations in different districts of Nagaland. Out of these four species belongs to family Agaricaceae, two belongs to Tricholomataceae and rest belongs to Boletaceae, Cantharellaceae, Russulaceae, Sarcoscyphaceae, Auriculariaceae, Polyporaceae, Schizophyllaceae, Pleurotaceae, and Lyophyllaceae. The selected species were analyzed for proximate analysis of nutritional values. The protein content varies from 22.50-44.93% and carbohydrates were recorded 32.43-52.07% in selected species. The documentation of wild edible mushrooms is very scanty in Northeast India. The key objective of the present study was to generate a database on macrofungal diversity, ecology, ethnomycology, utilization and nutrient status of important wild edible mushroom species of Nagaland, which forms a part of the food culture of the native peoples.